Opportunistic Behaviour of Foreign Fishers During Civil Conflicts and Civil Wars in Coastal African Countries - Salim Bensaf, Mohamed (Université d'Ottawa | University of Ottawa, 2015)
The negative economic consequences of civil wars and civil conflicts on countries wherein violence and instability become endemic are clear. Also, different researches mention the impacts of conflicts’ spread onto the geographically surrounding countries. This research investigates the sector-specific impacts that conflicts have on fisheries in neighbor countries. The study uses the reported maritime fish catch to investigate the possible effect of conflicts on fisheries as a result of population displacement, counter-insurgency policies, and foreign fishermen encroachment in marine territories. The analysis of data for 29 coastal African countries between 1970 and 2004 suggests a strong positive impact of the onset of civil conflict on the fish catch growth in neighbor countries. The research also finds a positive, but smaller, significant relationship between civil conflicts and fisheries in the bordering countries. Interestingly, the magnitude of these effects on fishing growth are largely higher than the impact of the GDP growth. The results also show that the termination of civil conflicts does not have a significant impact on the growth of fisheries. This research enriches the literature on the economic effects of civil conflicts as it attracts the attention of international fisheries and peace organizations to protect the coastal fisheries of these conflict afflicted regions given the regional social, political, and economic impacts of maritime resources.